2022
DOI: 10.1002/jsfa.11769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pollination on the composition of volatile compounds in Coffea arabica L.

Abstract: BACKGROUND Pollination enhances coffee quality at the material level, improves the symbolic attributes of coffee and promotes sustainability. The objective of this work was to quantify the composition of volatile compounds in roasted coffee produced in the presence and absence of biotic pollination, aiming at investigating the effects of pollination on the composition of volatile compounds in coffee beans. This is the first report of its kind in the literature. RESULTS The analysis of volatile compounds in roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The flavor, aroma, and texture of the coffee bean depend on many factors, including variety, geographical origin, climatic factors, maturation of the cherry, fermentation, drying, roasting, and storage conditions [7,8]. More recently, studies reported that pollination enhanced coffee's volatile compounds [9]. The aroma of the powdered coffee beans depends on these factors, where roasting is considered the final line of chemical modification of the aroma.…”
Section: Introductionmentioning
confidence: 99%
“…The flavor, aroma, and texture of the coffee bean depend on many factors, including variety, geographical origin, climatic factors, maturation of the cherry, fermentation, drying, roasting, and storage conditions [7,8]. More recently, studies reported that pollination enhanced coffee's volatile compounds [9]. The aroma of the powdered coffee beans depends on these factors, where roasting is considered the final line of chemical modification of the aroma.…”
Section: Introductionmentioning
confidence: 99%